HUBUNGAN KOMPETENSI LEADERSIP GURU PAI DAN TINGKAT DISIPLIN SISWA KELAS IX DI MTS DARUL ULUM CIHERANG PONDOK KABUPATEN BOGOR - Rahman, Muhamad Zandan Zaeni; Milla, Sri Nurul; Subki, Badruddin (FIKRAH, 2021)
Discipline in education is a must to get good learning outcomes. Therefore, based on information from the teacher at Mts Darul Ulum Ciherang Pondok in 2021 the authors found that most of the IX grade students experienced a lack of discipline level. So that the leadership competence of PAI teachers in guiding students in improving student discipline during learning is very much needed, because educators must be able to make students make decisions, solve problems, and have a leadership spirit so that students' disciplined attitudes will grow. This study aims to determine the relationship between leadership competence and the level of discipline of class IX students in a secondary school in Bogor Regency. This study uses a quantitative method by conducting a correlation test. The researcher obtained data from a sample of 89 class IX students through a questionnaire. The results of data analysis showed that the Pearson Correlation was 0.418, when viewed from the interpretation table, the results of 0.418 lie between 0.40-0.70. That is, the result of 0.418 is included in the criteria which is quite strong so that the researcher can conclude that there is a positive correlation between the X and Y variables with a moderate relationship. In addition, it is proven by a significance value of 0.000 which is smaller than 0.05. Thus, it can be concluded that between PAI teacher leadership competence (X) and the discipline level of Class IX students at Mts Darul Ulum Ciherang Pondok (Y) there is a significant and positive relationship. In other words, the better the leadership competence of PAI teachers, the higher the level of student discipline will be.